Shear-wave velocity structure underneath the city of Padang, Indonesia - Jeow, Ting Yong (2011)
Natural disaster like earthquake has always caused devastating effects to the ground as well as building structures. Research has also shown that rigidity of the soil profile plays a critical part in determining the level of damages caused. Hence this project aims to employ a low cost, time saving and non-destructive method to record the microtremor wave in Padang Indonesia, namely Microtremor Survey Method (MSM), in order to estimate the geological subsurface structure of the ground. The method requires a sensor to be placed according to an observation array of an equilateral triangle to record for microtremor waves which would be processed to estimate the Rayleigh wave dispersion curve. Subsequently, the shear wave velocity and thickness of each soil layers would be estimated through inversion. After which the subsurface structure of the soil layers will be generated using the estimated results. In this project, Spatial Autocorrelation (SPAC) methods are used for the processing of data obtained from the small array. It provides a more critical result as small array recording records wave that travels nearer to the surface.